Systematic Literature Review of Innovative Schools: A Map and a Characterization from Which We Learn - Eduardo Amaral Lomba; José Matias Alves; Ilídia Cabral (MDPI AG, 2022)
The traditional school model is subject to growing social pressure. The collective awareness of the need to find new pedagogical and organizational approaches has fueled the dynamics of school innovation. Over the last two decades, several schools have emerged worldwide bearing innovative models. The present study pursued two objectives: first-map the innovative schools worldwide, with students between 10/11 and 17/18 years old, referenced by academic publications; second-identify the dimensions of school innovation that those same academic publications indicate in the referenced schools. A systematic literature review was carried out in English, Portuguese, and Spanish between 2000 and 2021 in the search engines SCOPUS, Web of Science (WoS), EBSCO, Google Scholar, and RCAAP (Open Access Scientific Repositories of Portugal). There may be an increasingly broad consensus on the need for a change in the current school model, but are those so-called innovative schools more effective in promoting learning? The results obtained may raise further research to answer this question.